Fibroblast growth factor 21 is independently associated with severe hepatic steatosis in non‐obese HIV‐infected patients. (5th April 2019) - Praktiknjo, Michael; Djayadi, Natalie; Mohr, Raphael; Schierwagen, Robert; Bischoff, Jenny; Dold, Leona; Pohlmann, Alessandra; Schwarze‐Zander, Carolynne; Wasmuth, Jan‐Christian; Boesecke, Christoph; Rockstroh, Jürgen K.; Trebicka, Jonel
Abstract: Background: Severe hepatic steatosis shows a high prevalence and contributes to morbidity and mortality in human immunodeficiency virus (HIV) infected patients. Known risk factors include obesity, dyslipidaemia and features of metabolic syndrome. Fibroblast growth factor 21 (FGF‐21) is involved with hepatic glucose and lipid metabolism. This study aimed to evaluate FGF‐21 as a biomarker for severe hepatic steatosis in non‐obese HIV‐infected patients. Methods: This is a prospective, cross‐sectional, monocentric study including HIV‐infected out‐patients. Hepatic steatosis was measured via controlled attenuation parameter (CAP) using FibroScan 502 touch (ECHOSENS, France). Severe hepatic steatosis was defined at CAP ≥ 253 dB/m. Peripheral blood samples were collected and plasma was analysed for FGF‐21. Demographic and clinical characteristics were collected from patient's health records. Results: In total, 73 non‐obese HIV‐monoinfected patients were included in this study. Prevalence of severe hepatic steatosis was 41%. Patients with severe hepatic steatosis showed significantly higher levels of FGF‐21. Univariate analysis revealed FGF‐21, BMI, hyperlipidaemia, ALT levels and arterial hypertension as significant, while multivariate analysis showed only FGF‐21, arterial hypertension and ALT levels as significant independent risk factors for severe hepatic steatosis. Conclusion: This study presents FGF‐21 as an independent and stronger predictor of severe hepatic steatosis than blood lipids in HIV‐infected patients. Moreover, arterial hypertension and ALT levels predict severe steatosis even in non‐obese HIV‐monoinfected patients. Furthermore, this study supports existing metabolic risk factors and expands them to non‐obese HIV‐infected patients.